ANALISIS SALURAN DISTRIBUSI DAN EFISIENSI PEMASARAN PUPUK BERSUBSIDI DI KECAMATAN SELAKAU KABUPATEN SAMBAS (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2012)
ABSTRACT Have been done conducted by research with the title analyse the channel of distribution and marketing efficiency fertilize to subsidize in subdistrict selakau, regency sambas to know the distribution process fertilize to subsidize from Petrochemical PT Pusri and PT of Gresik to paddy farmer and to know the level of marketing expense, swampy forest price ( price spread) and share margin which is in accepted by each channeling institute fertilize to subsidize. Data collected with the observation and interview to farmer. this Research population is farmer, producer, distributor, formal retailer and also retailer. election Sampel ( responden) done conducted by determining sampel farmer ( simple random sampling), sampel merchant determined by snowball is sampling.Result of research show, that pattern of distribution or channeling fertilize to subsidize in subdistrict of selakau of regency sambas of disagree with decision of SK Menperindak No. 17/M-DAG/PER/6/2011 that is first the than producer to distributor, laterthen to formal retailer then to retailer and last to consumer. Channeling fertilize to subsidize done conducted in subdistrict selakau indicate that the biggest margin value released by distributor institute whereabout fertilize the urea Rp. 400.16 / Singk of Za Rp. 1.136.16 / Singk of SP36 Rp. 522.16 / Singk of NPK Rp. 298.16 / Organic singk of Rp. 400.2 / Singk institute this represent the inefficient marketing channel of own the high in comparing formal institute retailer and retailer . While smallest marketing expense in releasing by institute of retailer whereabout to fertilize the urea Rp. 345 / singk of Za Rp. 345 / singk SP 36 Rp. 432 / singk of NPK Rp. 445 / organic singk of Rp.545 / singk, hence earn in concluding that channel of marketing of retailer is efficient marketing channel if in comparing with channel of marketing of formal retailer and distributor of karna own the low and obtain get the highest value share margin. Keywords: Margin, Efficiency, fertilize to subsidize.